ChemInform Abstract: Laxiflorol A, the First Example of 7, 8:15, 16‐Di‐seco‐15‐nor‐21‐homo‐ent‐kauranoid from Isodon eriocalyx var. laxiflora. Issue 24 (June 2015) - Wang, Wei‐Guang; Tang, Jian‐Wei; Shi, Yi‐Ming; Du, Xue; Li, Xiao‐Nian; Wu, Hai‐Yan; Jiang, Hua‐Yi; Li, Yan; Pu, Jian‐Xin; Sun, Han‐Dong
Abstract: The isolation and structure elucidation of laxiflorol A (I), which is the first example of 7, 8:15, 16‐di‐seco‐15‐nor‐21‐homo‐ent‐kauranoid, and its precursor analogue laxiflorol B (II) from the leaves of Isodon eriocalyx var.